The Effect of Lavender Essential Oil Aromatherapy on the Anxiety of Endoscopy Candidates: A Clinical Trial - A Monfared; M Mirzaee Jirdehi; F Mansour Ghanaei; F Joukar; E Kazemnezhad Leyli (Iran University of Medical Sciences, 2020)
Background & Aims: Endoscopy is known to cause significant anxiety in the patients in the clinical setting. Aromatherapy is a complementary medicine technique used to alleviate anxiety. The present study aimed to assess the effect of aromatherapy with lavender essential oil on the preoperative anxiety of endoscopy candidates in Iran. Materials & Methods: This clinical trial was conducted at the endoscopy department of Razi Hospital in Rasht, Iran during January 2018-August 2019. The sample population included 70 patients who were selected via convenience sampling based on the inclusion criteria and randomly divided into two groups of intervention and placebo. After completing the informed consent form, data were collected using a demographic questionnaire and Spielberger state-trait anxiety inventory. One hour before endoscopy, the intervention group received aromatherapy with 10% lavender essential oil, and the placebo group received aromatherapy with placebo for 30 minutes. The anxiety inventory was completed again before endoscopy. Data analysis was performed in SPSS version 21 using statistical tests (P<0.05). Results: The mean age of the patients was 47.12±16.75 years, and the majority of the participants were female. After the intervention, the mean score of anxiety decreased in the intervention group compared to the placebo group, and the difference was considered significant (P=0.001). Conclusion: According to the results, aromatherapy with lavender essential oil was effective in the reduction of pre-endoscopic anxiety in the patients. Considering the low cost, safety, and simplicity of this method, aromatherapy could be used as a complementary measure to reduce anxiety in patients before endoscopy.